PERKEMBANGAN PENDAPATAN DAERAH EMPAT KABUPATEN TERTINGGAL DI PROVINSI JAWA TIMUR - Rudy Badrudin (Jurnal Riset Manajemen dan Bisnis, 2013)
This study examined balance funds and the own-source revenue (PAD) in four regencies in East Java Province based on the data of year 2007 to 2011. Balance funds consist of the Shared Revenue Funds (DBH), the General Allocation Fund (DAU), and the Specific Allocation Fund (DAK). Based on research method using hypothesis test for means (ANOVA), the results show that PAD has difference significant according regency and year; DBH, DAU, and DAK have difference significant according regency; DBH, DAU, and DAK have no difference significant according year. Keywords: own-source revenue, shared revenue fund, general allocation fund, specific allocation fund